2018
DOI: 10.1111/geb.12769
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and species‐level predictions of road mortality risk using trait data

Abstract: Aim:Collisions between wildlife and vehicles are recognized as one of the major causes of mortality for many species. Empirical estimates of road mortality show that some species are more likely to be killed than others, but to what extent this variation can be explained and predicted using intrinsic species characteristics remains poorly understood. This study aims to identify general macroecological patterns associated with road mortality and generate spatial and species-level predictions of risks. Location:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
74
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(91 citation statements)
references
References 48 publications
6
74
2
2
Order By: Relevance
“…Therefore, it is important to understand which species are especially vulnerable to roadkill, under which environmental and road conditions roadkill is most prevalent, and how roadkill is spatially distributed. Roadkill does not affect species randomly, as variability in mortality rates between species is linked to species traits; especially those related to movements, microhabitat use, and thermal strategies (González-Suárez, Zanchetta Ferreira, & Grilo, 2018). For example, species that are large and slow-moving are likely to be more prone to becoming the victim of vehicle collision, than species that are small and fast-moving (Forman et al, 2003;González-Suárez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is important to understand which species are especially vulnerable to roadkill, under which environmental and road conditions roadkill is most prevalent, and how roadkill is spatially distributed. Roadkill does not affect species randomly, as variability in mortality rates between species is linked to species traits; especially those related to movements, microhabitat use, and thermal strategies (González-Suárez, Zanchetta Ferreira, & Grilo, 2018). For example, species that are large and slow-moving are likely to be more prone to becoming the victim of vehicle collision, than species that are small and fast-moving (Forman et al, 2003;González-Suárez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Roadkill does not affect species randomly, as variability in mortality rates between species is linked to species traits; especially those related to movements, microhabitat use, and thermal strategies (González-Suárez, Zanchetta Ferreira, & Grilo, 2018). For example, species that are large and slow-moving are likely to be more prone to becoming the victim of vehicle collision, than species that are small and fast-moving (Forman et al, 2003;González-Suárez et al, 2018). With regard to species-specific mortality rates, species that have higher local abundances are more likely to be prone to vehicle collision (Forman et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Implementing expert-predicted infrastructure impacts into conservation prioritization re-ranked the region's conservation priorities (Figure 3). Experts identified that species within different threat-similarity groups would be differently affected by infrastructure, supporting findings that ecological traits affect vulnerability to infrastructure (González-Suárez et al, 2018;Rytwinski & Fahrig, 2012). For example, experts estimated that frogs would experience greater reductions in habitat quality close to roads than most other groups.…”
Section: Discussionmentioning
confidence: 77%
“…Due to the predictive nature of the regression tree imputation approach, the estimated values will differ slightly each time. To capture this imputation uncertainty and to converge on a reliable result, we repeated the process 15 times, resulting in 15 trait datasets (González-Suárez, Zanchetta Ferreira, & Grilo, 2018;van Buuren & Groothuis-Oudshoorn, 2011). We take the mean trait values across the 15 datasets for subsequent analyses.…”
Section: Multiple Imputationmentioning
confidence: 99%